KONTRASTIF MAKNA ADJEKTIVA YASASHII（優しい） DALAM BAHASA JEPANG DAN BAIK DALAM BAHASA INDONESIA - Hastuti, Wina Widia; Dwi Irfandhi, Meizal; Tamara, Yasmin (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2026)
This research aims to identify the similarities and differences in terms of meaning or semantically between the yasashii adjective in Japanese with the baik adjective in Indonesian. The methods used in this research include the method of listening and recording in the data collection stage and the contrastive analysis method using Koyanagi's theory in the data analysis stage, which then the results of the analysis will be presented in words in the form of descriptions. The data sources used in this research are jitsurei obtained from Asahi Shimbun and Kompas newspapers accessed online. The result of this research is five similarities, six differences and one new finding. The meanings that have similarities are the meaning of caring, kindness or virtue, not giving bad influence, useful or effective and not malicious. While the differences in meaning found are lucky or fortunate, cured, congratulations, appropriate, comparative statements and approval. One new finding found is the equivalent of the yasashii adjective with the word lembut adjective in Indonesian. The linguistic phenomena found are Ichii, Yuugou and Shinki phenomena